Validation Miniature Hemodialysis Tools: STEM Project of Human Excretion Systems (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2022)
The aim of this study was to validate the development of miniature hemodialysis tools for STEM projects in the learning of human excretion systems. The development of these miniature hemodialysis tools can help learners more easily understand the mechanism of dialysis in the study of human excretion systems. There are four aspects of assessing the validity of experimental tools; these aspects are relevance to the topic taught, ease, clarity and neatness, and size according to the learning environment. This assessment consists of four validation items that have 11 assessment indicators. Each assessment indicator has been scored as ≥ 3.00 by expert lecturers. This tool has been validated with an average assessment given by expert lecturer validators I, II and professional teachers, respectively, 3.46, 3.67, and 3.40. By averaging the ratings of the three validators, the validation score of this tool is 3.51. This means that all assessment criteria contained on the validation sheet have been met by the miniature hemodialysis tools.